Pengaruh Celebrity Endorser, Kepercayaan Konsumen, Dan Kepuasan Konsumen Terhadap Minat Pembelian Ulang Pada Produk Scarlett Whitening: Studi Kasus Pada Konsumen Scarlett Whitening di Kabupaten Banjarnegara - Natalia Ratna Ningrum; Anindita Imam Basri; Rizka Aulia Revani; Hanindya Amelia Putri (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
Abstract This study aims to determine the effect of celebrity endorser, consumer trust and consumer satisfaction on repurchase interest in Scarlett Whitening products. This research was conducted in Banjarnegara Regency, Central Java from October to November 2021. This research is a quantitative study with a sample of 154 respondents. The sampling technique used non-probably sampling using snowball sampling and purposive sampling. Data was collected by distributing questionnaires through Google Form. This study uses multiple linear regression analysis techniques. The results of this study conclude that partially celebrity endorser has a positive and significant effect on repurchase intention, consumer trust has a positive and significant effect on repurchase interest, and consumer satisfaction has a positive and significant effect on repurchase interest. Simultaneously celebrity endorser, consumer trust and consumer satisfaction have a positive and significant effect on repurchase intention with a sig value of 0.000 indicated. The effect of celebrity endorser, consumer trust and consumer satisfaction on repurchase interest can be seen with the Adjusted R Square value of 58.3% while the remaining 41.7% is influenced by other variables outside of this study.